Hereditary angioedema (HAE) in patients with C1 inhibitor deficiency – Cracow register - Obtułowicz, Krystyna; Obtułowicz, Piotr; Kapusta, Maria (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
102 patients suffering from Hereditary angioedema (HAE) belonging to 41 families have been studied. 96 patients (95.1%) had type I HAE characterized by low antigenic level and low functional activity of C1 inhibitor. 6 patients (4.9%) had type II HAE related to low functional activity of C1 inhibitor. The swelling of subcutaneous tissue was observed in 74 patients and the bowel muccose in 38 patients. The infusions of C1 inhibitor (Berinert P) were very effective and good tolerated in the therapy of 50 sever angioedema attacks. 15 patients were given long prophylactic treatment with Danazol with full success but side effects were very often in many patients especially in women.